(untitled) (Colombia Medica, 2013)
Introduction: HIV/AIDS is a global health priority. About 40% of new infections occur among heterosexual youth by means of sexual contact. In Cali, commune 13, 15 and 20 account for 11.5% of the prevalent cases and 18.0 % of incident cases. Objective: To establish any differences in risk behaviors for HIV among young people 15-24 yrs of age from two areas of Cali, Colombia. Methods: We carried out a cross-sectional study among young people between 15 and 24 yrs of age in these communes. The selection was done with a two-stage probability sampling. We estimated the prevalence of sexual relationships without condom usage, sex with multiple partners, and sex under the effects of alcohol and through logistical regression we identified the related factors. Results: In communes 13, 15 and 20, the prevalence of unprotected sexual relationships in the last 12 months and the prevalence of sex with two or more partners was 70%; and 38% of young people had sex under the effects of alcohol. In both areas, the intention was positively related to the risk behaviors. We found socio-demographic factors, intentions, and beliefs that increase the opportunity to display these behaviors. The effect of these factors differs by commune. Conclusions: We observed a high prevalence of risk behaviors for HIV related to socio-demographic factors, intentions and beliefs that warrant interventions appropriate for local realities.